A Threat to Geoscience Education: Creationist Anti-Evolution Activity in Canada - Wiles, Jason (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2006)
SUMMARY The rejection of biological and geological evolution is a pervasive problem in science education. Recent events in the United States have brought anti-evolution activity to the forefront in media coverage of science education, but Canadians are often unaware that such creationist, anti-evolution activity is present in Canada as well. In this article, various foreign and Canadian-based anti-evolution efforts that threaten biology and geoscience education are discussed. These creationist organizations and their activities may adversely influence Canadian science curricula and public understanding of evolution and science in general.